Use of novel polysaccharides in textile printing - Banerjee, Apurba, author; Sarkar, Ajoy Kumar, advisor; Miller, Nancy, committee member; Sparks, Diane, committee member; Kissell, Kevin, committee member (Colorado State University. Libraries, 2013)
Polysaccharides such as starches are utilized in textile applications for sizing, textile printing as a thickener, finishing agent and textile coating. Good sources of starch are corn, potato, maize and cereals such as millet and sorghum. In the United States, proso millet (Panicum miliaceum) and sorghum (Sorghum bicolor L. Moench) are two economically important crops, yet the current utilization of proso millet and sorghum are in low-end uses such as bird seed and livestock feed. This research is directed at utilizing starch extracted from proso millet and sorghum for value-added application in textile industry such as thickeners in textile printing. The current work described in this thesis discusses an optimum method of extracting starch from both proso millet and sorghum cereal grains followed by characterization of starch using different physicochemical techniques like XRD, DSC, amylose content, spectrophotometric analysis of starch color, paste clarity analysis, rheological analysis, shear stability, stability to storage and starch swelling capacity. The starches were then incorporated as a thickener in a textile print formulation and print quality was evaluated on the basis of crocking fastness, bending length and washing fastness. The color depth of the textile print was determined according to the Kubelka- Munk equation. The results of the detailed analysis of the starches show that both proso millet and sorghum could be utilized effectively as thickeners in textile printing. Both starches had desirable properties of a good thickener such as excellent paste clarity, adequate viscosity and high solubility and crystallinity. The properties of the printed textiles using millet and sorghum starches were comparable to that of sodium alginate thickener further demonstrating the potential of these grains in value-added applications.
Keywords: characterization; sorghum; textile printing; extraction; polysaccharide; Proso millet